Value, Satisfaction and Word of Mouth for a Retail Brand - Frederico, Elias (2014)
This study aimed to identify the antecedents of value, satisfaction and worth of mouth (WOM) for franchise and flagship store shoppers. The literature review and a in-depth interview with the flasgship store manager indicated that brand and product aspects, as well the store environment and services aspects influence value, satisfaction and WOM. Then, a structural model was adjusted and tested with data collected from a survey with 275 consumers. Findings indicate that WOM and satisfaction are mediated by hedonism and utilitarism. Brand and store aspects are determinants of hedonic value and store aspects are associated with utilitarism. In addiction, flagship shoppers are more satisfied and tend to recommend the brand more than franchise shoppers.